Intermittent hypoxic exposure does not improve sleep at 4300 m - Jones, J. E.; Muza, S. R.; Fulco, C. S.; Beidleman, B. A.; Tapia, M. L.; Cymerman, A. (High Altitude Medicine & Biology, 2008)
The purpose of this study was to determine in sea-level residents if 6 to 7 consecutive days of normobaric intermittent hypoxic exposure (IHE) (hypoxia room: 2-h ambient PO2 = 90 mmHg sedentary and 1-h ambient PO2 = 110 mmHg exercising at 80 ± 5% of maximum heart rate) improved sleep quality (awakenings per hour) and quantity at altitude (4300 m). We hypothesized that IHE would improve sleep arterial oxygen saturation (SaO2) levels and decrease desaturation events, thereby contributing to improvements in sleep quality and quantity during subsequent exposure to high altitude. Ten sea-level residents (mean ± SE: 22 ± 1 yr, 179 ± 2 cm, 79 ± 3 kg) were assigned to an IHE group and six to a SHAM group (20 ± 0.5 yr, 180 ± 3 cm, 77 ± 4 kg). Sleep quantity, SaO2, and heart rate (HR) were monitored at sea level and during high altitude (i.e., 4300 m in a hypobaric chamber) before pretest (PRE-T) and 60 h after posttest (POST-T) for the last IHE or SHAM treatment. Over the 6 to 7 days of IHE, resting SaO2 increased from 75 ± 1% to 81 ± 3% in the IHE group, while the SHAM group remained at 98 ± 1%. From PRE-T to POST-T at 4300-m exposure, both the IHE and SHAM groups had significantly higher sleep SaO2, fewer desaturation events per hour, and an increase in the percentage of time asleep while sleeping (sleep percent). The IHE group, but not the SHAM group, had significantly lower sleep HR and a trend to more awakenings during the POST-T 4300-m exposure. These results indicate that although IHE treatment induced significant ventilatory acclimatization, relative to the SHAM group, IHE did not further improve sleep SaO2 quality and quantity following rapid ascent to 4300 m. Rather, it is likely that the acquired ventilatory acclimatization was lost in the 60 h between the last IHE session and the POST-T altitude exposure.